Clinical Outcome of CT-Guided Stereotactic Ablative Brachytherapy for Unresectable Early Non-Small Cell Lung Cancer: A Retrospective, Multicenter Study - Ji, Zhe; Huo, Bin; Liu, Shifeng; Liang, Qinghua; Xing, Chao; Hu, Miaomiao; Ma, Yanli; Wang, Zhe; Zhao, Xinxin; Song, Yuqing; Wang, Yufeng; Han, Hongmei; et al. (Frontiers in Oncology, 2021)
Objective: To analyze the efficacy and safety of low dose rate stereotactic ablative brachytherapy (L-SABT) for treatment of unresectable early-stage non-small cell lung cancer (NSCLC). Methods: Data of patients with early-stage NSCLC who received CT-guided L-SABT (radioactive I-125 seeds implantation) at eight different centers from December 2010 to August 2020 were retrospectively analyzed. Treatment efficacy and complications were evaluated. Results: A total of 99 patients were included in this study. Median follow-up duration was 46.3 months (6.1-119.3 months). The 1-year, 3-year and 5-year local control rates were 89.1%, 77.5% and 75.7%, respectively. The 1-year, 3-year and 5-year overall survival rates were 96.7%, 70.1% and 54.4%, respectively. Treatment failure occurred in 38.4% of patients. Local / regional recurrence, distant metastasis and recurrence combined with metastasis accounted for 15.1%, 12.1% and 11.1%, respectively. Pneumothorax occurred in 47 patients (47.5%) with 19 cases (19.2%) needed closed drainage. The only radiation-related adverse reaction was two cases of grade 2 radiation pneumonia. KPS 80–100, T1, the lesion was located in the left lobe, GTV D90 ≥150 Gy and the distance between the lesion and chest wall was < 1 cm were associated with better local control (all P < 0.05); on multivariate analysis KPS, GTV D90 and distance between the lesion and chest wall were independent prognostic factors for local control (all P < 0.05). KPS 80–100, T1, GTV D90 ≥150 Gy and the distance between the lesion and chest wall was < 1 cm were also associated with better survival (all P < 0.05); on multivariate analysis KPS, T stage and GTV D90 were independent prognostic factors for survival (all P < 0.05). Conclusion: L-SABT showed acceptable efficacy in the treatment of unresectable early-stage NSCLC. But the incidence of pneumothorax is high. For patients with T1 stage and lesions <1 cm from the chest wall may have better efficacy. Prescription dose greater than 150Gy may bring better results.